PENGUATAN KOMPETENSI TEKNOLOGI DAN KETERAMPILAN BACA TULIS AL-QUR’AN BAGI SISWA SEKOLAH DASAR DAN MENENGAH DI DUKUH SLOROK, DESA CEPOKO, KECAMATAN NGRAYUN, KABUPATEN PONOROGO - Muhammad Hanif Rifai; Jamilah Karaman; Akhmad Tio Febriansyah; Dimas Nazla Prasetianto; Lukman Teguh Priyatin (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
The low level of digital literacy among students and teachers in rural areas remains a challenge, while the ability to read and write the Qur’an (BTQ) is still uneven. Through the Thematic Community Service Program (KKN) Group 1 of the Faculty of Engineering, Universitas Muhammadiyah Ponorogo, held in Dukuh Slorok, Cepoko Village, Ngrayun District, this activity aimed to improve basic technological competencies (Microsoft Word, Canva, and Artificial Intelligence) and to strengthen BTQ skills among elementary and junior high school students. The implementation method used a participatory approach through socialization, hands-on practice, and intensive mentoring. Evaluation was conducted through pre- and post-tests, teacher questionnaires, and observation of students’ BTQ progress. The results showed increased student skills in document processing, teachers’ ability to create digital learning media, and improvement in students’ Qur’an reading and writing proficiency. The program demonstrates that digital literacy and religious education can work synergistically and provide dual benefits.